"Chrysler Pulled the Trigger": The Affective Politics of Insanity and Black Rage at the Trial of James Johnson, Jr. Issue 2 (14th March 2016) - McCann, Bryan J.
Abstract : In 1970, black autoworker James Johnson, Jr., fatally shot three people at Chrysler's Eldon Avenue Gear and Axel Plant in Detroit. The shooting occurred three years after a devastating urban uprising and in the context of black militant labor organizing in local automotive plants. After a legal defense arguing racism and labor exploitation provoked his actions, Johnson was found not guilty for reasons of insanity. In this essay, I attend to the defense strategy that attempted to retain the political critique implicit in Johnson's "black rage" while working within the constraints of jurisprudential and clinical notions of "insanity." The Johnson case suggests that the mobilization of black affect is an always-ambivalent endeavor that can enable radical critique and political practice, while also subordinating black rhetorical agency.